2008
DOI: 10.1186/1477-7517-5-35
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of HIV infection among homeless and street-involved Aboriginal youth in a Canadian setting

Abstract: Aboriginal people experience a disproportionate burden of HIV infection among the adult population in Canada; however, less is known regarding the prevalence and characteristics of HIV positivity among drug-using and street-involved Aboriginal youth. We examined HIV seroprevalence and risk factors among a cohort of 529 street-involved youth in Vancouver, Canada. At baseline, 15 (2.8%) were HIV positive, of whom 7 (46.7%) were Aboriginal. Aboriginal ethnicity was a significant correlate of HIV infection (odds r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 16 publications
3
25
0
Order By: Relevance
“…74 Strong relationships between drug use, homelessness, and risky injecting practices are evident among Canada's Indigenous peoples and are thought to account, at least in part, for the elevated HIV prevalence and incidence observed among Aboriginal PWID in this setting. 53,72,75,76 Similarly, ANSPS data collected between 1998 and 2008 and stratified by Indigenous Australian origin documented significantly higher rates of both anti-HCV and key injecting risk behaviors among these participants relative to their non-Indigenous counterparts. 77 Although housing information was not available for this (previous) analysis, the consistency between the present results and those derived from other settings which demonstrate strong associations between housing and risk among Indigenous peoples suggests that the elevated HCV prevalence and injecting risk behaviors previously documented among Aboriginal ANSPS participants 77 is likely to be at least partially accounted for by housing inequities experienced by Indigenous and non-Indigenous ANSPS participants.…”
Section: Discussionmentioning
confidence: 98%
“…74 Strong relationships between drug use, homelessness, and risky injecting practices are evident among Canada's Indigenous peoples and are thought to account, at least in part, for the elevated HIV prevalence and incidence observed among Aboriginal PWID in this setting. 53,72,75,76 Similarly, ANSPS data collected between 1998 and 2008 and stratified by Indigenous Australian origin documented significantly higher rates of both anti-HCV and key injecting risk behaviors among these participants relative to their non-Indigenous counterparts. 77 Although housing information was not available for this (previous) analysis, the consistency between the present results and those derived from other settings which demonstrate strong associations between housing and risk among Indigenous peoples suggests that the elevated HCV prevalence and injecting risk behaviors previously documented among Aboriginal ANSPS participants 77 is likely to be at least partially accounted for by housing inequities experienced by Indigenous and non-Indigenous ANSPS participants.…”
Section: Discussionmentioning
confidence: 98%
“…3). Prevalence estimates were generally found to be high among Aboriginal peoples who use drugs and ranged from 0.8 to 38.0% [16,54] compared with 2.0 to 21.2% among non-Aboriginal peoples who use drugs in these studies [17,30] (Fig. 3a).…”
Section: Hiv Prevalencementioning
confidence: 95%
“…Studies have consistently reported that Aboriginal youth demonstrate more sexual risk behaviours and higher prevalence rates of stis and hiv. In Vancouver, Aboriginal homeless youth were nearly three times more likely to be hiv positive than non-Aboriginal youth (Marshall et al 2008). In Toronto, a higher proportion of Aboriginal youth (5.0%) and black youth (4.3%) self-reported their hiv status as positive compared to white youth (3.0%; Linton et al 2009).…”
Section: Socio-demographic Risk Factorsmentioning
confidence: 97%
“…Prevalence rates were also high for hepatitis B and herpes simplex virus 2 (hsv-2), the primary cause of genital herpes. Studies in Toronto, Montreal and Vancouver have reported high hiv prevalence among homeless youth, ranging from 1.9 percent to 2.8 percent (DeMatteo et al 1999;Marshall et al 2008;Roy et al 2000). Comparable data on hiv prevalence rates among youth in the general population are not available, likely because this age group makes up an extremely small proportion (approximately 3.5%) of the total number of hiv cases in Canada (phac 2007).…”
Section: Prevalence Of Sexually Transmitted Infections Hiv and Pregnmentioning
confidence: 99%
See 1 more Smart Citation